Primary peg-filgrastim prophylaxis versus filgrastim given "on demand" for neutropenia during therapy with cladribine for hairy cell leukemia. (July 2019) - Tadmor, Tamar; Levy, Ilana; Herishanu, Yair; Goldschmidt, Neta; Bairey, Osnat; Yuklea, Mona; Shvidel, Lev; Fineman, Riva; Aviv, Ariel; Ruchlemer, Rosa; Braester, Andrei; Dally, Najib; et al.
Highlights: Infectious complications post-cladribine treatment remain high. Primary peg-filgrastim prophylaxis compared to filgrastim given on demand. Both types of G-CSF are justifiable, and the choice remains at the physician's discretion. Abstract: Background: Major advances in the treatment of patients with hairy cell leukemia (HCL) have been made following the introduction of purine analogues. The major significant short-term toxicity of cladribine therapy are neutropenia and neutropenic fever (NF) which may be life-threatening. Aim: In this retrospective study, we compared the incidence and duration of neutropenia and hospitalization in patients with HCL treated with cladribine followed by peg-filgrastim as primary prophylaxis versus daily filgrastim given "on demand" according to absolute neutrophil count (ANC). Methods: Medical records of patients with HCL diagnosed and followed in 12 medical centers in Israel during 1985–2015 were examined for details of disease at diagnosis. The efficacy of peg-filgrastim and filgrastim was assessed by evaluating the incidence of neutropenia (ANC < 1.0 × 10 [9 ]/L), number and length of hospitalizations, and number of days from the last day of therapy to recovery of ANC to >1.0 × 10 [9 ]/L. Results: The study population included 202 patients with HCL, 159 of whom (80.7%) were treated with cladribine; 78 patients (49%) required hospitalization for the administration of broad-spectrum antibiotics due to NF. Twenty-eight (19%) patients were treated with peg-filgrastim as primary prophylaxis, while 74 (64%) received filgrastim "on demand" due to neutropenia. Median length of hospitalization, and nadir duration were 8 and 18 days respectively (p = 0.71, p = 0.44). Conclusions: Infectious complications post-cladribine treatment remain high. No difference was found in terms of incidence of NF, number of febrile days, and nadir duration in patients receiving primary peg-filgrastim prophylaxis compared to filgrastim given on demand. Both approaches are justifiable, and the choice remains at the physician's discretion.